2019
DOI: 10.1136/bjophthalmol-2019-314466
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and selective biomarker expression in human meibomian glands

Abstract: Background/aimsMeibomian gland dysfunction (MGD) is the most common form of evaporative dry eye disease, but its pathogenesis is poorly understood. This study examined the histopathological features of meibomian gland (MG) tissue from cadaver donors to identify potential pathogenic processes that underlie MGD in humans.MethodsHistological analyses was performed on the MGs in the tarsal plates dissected from four cadaver donors, two young and two old adults, including a 36-year-old female (36F) and three males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The study finding suggested that the central ductal epithelia’s abnormal differentiation and proliferation may be responsible for the ductal obstruction. This study also showed that ductal epithelial abnormal differentiation and proliferation alone, barring any conspicuous hyperkeratinization, can obstruct the meibomian glands ( 93 ). The decline in acinar cell proliferation and renewal was purported to be the underpinning instigator of meibomian gland atrophy with aging ( 93 ).…”
Section: Keratins As Candidate Biomarkers For Meibomian Gland Dysfunc...mentioning
confidence: 55%
See 4 more Smart Citations
“…The study finding suggested that the central ductal epithelia’s abnormal differentiation and proliferation may be responsible for the ductal obstruction. This study also showed that ductal epithelial abnormal differentiation and proliferation alone, barring any conspicuous hyperkeratinization, can obstruct the meibomian glands ( 93 ). The decline in acinar cell proliferation and renewal was purported to be the underpinning instigator of meibomian gland atrophy with aging ( 93 ).…”
Section: Keratins As Candidate Biomarkers For Meibomian Gland Dysfunc...mentioning
confidence: 55%
“…This study also showed that ductal epithelial abnormal differentiation and proliferation alone, barring any conspicuous hyperkeratinization, can obstruct the meibomian glands ( 93 ). The decline in acinar cell proliferation and renewal was purported to be the underpinning instigator of meibomian gland atrophy with aging ( 93 ). This evidence shows that overexpression of hyperproliferative keratins in meibum may be potential biomarkers to detect obstructive MGD accurately ( 93 ).…”
Section: Keratins As Candidate Biomarkers For Meibomian Gland Dysfunc...mentioning
confidence: 55%
See 3 more Smart Citations